An analysis of naturalistic interactions of a child with developmental delay / Jasvin Kaur Sidhu Harnek Singh - Jasvin Kaur Sidhu , Harnek Singh (2019)
Developmental Delay (DD) is a condition whereby a child fails to meet expected milestones for their actual or adjusted age. Children with DD has been associated with problems such as learning disabilities, intellectual disabilities, and language impairment. The main aim of this study is to explore naturally occurring interactions between an 8 years old female child, Manny with DD and her siblings so as to provide insights into how the child functions in her natural environment while interacting with her siblings. Employing Conversation Analysis (CA), the recurring patterns as well as the deviations in the interaction of Manny and her siblings are identified and analysed. The findings of this study reveal that conflict during routine play at home often leads to physical aggression displayed by Manny towards her siblings. Possibly due to her lack of language resources, Manny’s siblings act in a manner that is seen disaffiliating towards her and this resembles as bullying among siblings. Manny often initiates to play with her siblings but disagrees with them and even resorts to aggression when she does not get it her way. Outside the home environment, Manny frequently displays aggression and behaves in a physically threatening manner towards her siblings when they do not comply with her demands. In other routine activities, Manny is able to participate and collaborate with her siblings during interaction. One of the noteworthy findings of this study is that Manny’s siblings assist and facilitate her during interaction.